Household food security is associated with early childhood language development: Results from a longitudinal study in rural Bangladesh - Saha, Kuntal K.; Tofail, F.; Frongillo, Edward A.; Rasmussen, K. M.; Arifeen, S. E.; Persson, L. A.; Huda, S. N.; Hamadani, J. D. (Wiley, 2010)
Background  Although household food security (HHFS) has been linked to academic performance in school children, its association with early childhood development has received less attention, particularly in low‐income countries. We investigated the association of HHFS with subsequent language development of children at 18 months of age in rural Bangladesh.Methods  We followed 1439 infants born in 2002–2003 to the mothers in Maternal and Infant Nutrition Intervention in Matlab study, a large intervention trial conducted in rural Bangladesh. A HHFS scale was created from data collected from mothers during pregnancy. At 18 months, children's language (expression and comprehension) development was assessed using a Bengali adaptation of MacArthur's Communicative Development Inventory which was based on mothers' report of their children's ability to comprehend and express words in different categories. General linear regression models were used to examine the association between HHFS and language development at 18 months of age adjusting for potential confounders.Results  Household food security was associated with language comprehension (B = 0.19, 95% CI = 0.09, 0.30, P < 0.001) and expression (B = 1.01, 95% CI = 1.00, 1.02, P < 0.01) at 18 months of age. Mean language comprehension and expression at 18 months of the children in higher quartiles of HHFS were higher (P < 0.05) than those of the children in lower quartiles.Conclusions  Household food security is positively associated with subsequent language development of rural Bangladeshi children. Early language development has been reported to predict later child development. Therefore, strategies to ensure HHFS status in Bangladesh and similar settings should be considered for optimum child development.